Multilevel surgery in moderate to severe obstructive sleep apnea patients - Jumroon Tungkeeratichai (2018)
© 2014, Jaypee Brothers Medical Publishers (P) Ltd. All rights reserved. Objective: The aim of this study was to investigate the objective and subjective effectiveness of multilevel surgery, i.e. combined lingualplasty with new technique of partial posterior glossectomy (PPG) and uvulopalatopharyngoplasty in moderate to severe obstructive sleep apnea (OSA) patients. Study design and setting: Retrospective study of 60 OSA patients undergoing multilevel surgery for the treatment of moderate to severe OSA. Results: Preoperative mean apnea hypopnea index (AHI) was 57.5 events/h and preoperative mean lowest SpO2was 79.1%. After multilevel surgery, postoperative mean AHI significantly decreased to 29.7 events/h (p < 0.001) and postoperative mean lowest SpO2increased to 84.4% (p < 0.001). Patients had postoperative follow-up assessments for 1 to 3 years. Results of surgery was classified as curative in 35/60 (58.3%) of patients, and as effective, i.e. postoperative AHI less than preoperative AHI in 52/60 patients (86.7 %). Surgery was ineffective in 8/60 (13.3%) patients. Early postoperative complications comprised early velopharyngeal insufficiency (VPI) 20% (12/60), dysarthria 20% (12/60) and wound dehiscence 3.33% (2/60) but without serious complications after 1 year. Conclusion: Combined lingualplasty (with new PPG) and uvulopalatopharyngoplasty (UPPP) as multilevel surgery can be an effective treatment of choice for patients with moderate to severe OSA. No mediumterm serious complication was found.